Membangun Keterampilan Internet Cerdas dan Bijak Bermedia Sosial Bagi Anak dan Remaja Sebagai Upaya Perlindungan Data Pribadi dan Pencegahan Kejahatan Siber - Reno Rahmadiansyah Srg (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
The rapid advancement of information and communication technology has significantly impacted the lives of children and adolescents. While social media offers numerous benefits, its irresponsible use can lead to risks of personal data abuse and cybercrime. This study aims to develop smart and wise internet skills in social media for children and adolescents as an effort to protect personal data and prevent cybercrime. The research employs a qualitative approach with case studies in schools. The findings indicate that proper digital literacy education can enhance awareness among children and adolescents regarding existing risks and equip them with skills to use social media safely. This recommendation is crucial to be implemented in the educational curriculum to create a safer and more responsible generation in using technology.